Kejahatan Online Marketplace dalam Kriminologi dan Pengembangan Hukum Pidana Indonesia - Syah Awaluddin; Evy Savitri Gani; Supriadin Sisin; La Rusman; M. Ramli Tubaka (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
The rapid growth of online marketplaces in Indonesia has brought significant economic opportunities but also posed new challenges in the realms of criminal law and criminology. This study aims to analyze online marketplace crimes from a criminological perspective and examine the development of Indonesia's criminal law to address these challenges. Utilizing a qualitative approach with a literature review method, this research explores various types of online marketplace crimes, including fraud, identity theft, intellectual property violations, and tax evasion. The study applies criminological theories such as Strain Theory, Rational Choice Theory, Routine Activity Theory, Social Control Theory, and Social Learning Theory to understand the motivations and behaviors of offenders in digital transactions. The findings indicate that the legal framework in Indonesia, including the Electronic Information and Transactions Law (UU ITE) and Consumer Protection Regulations, still contains gaps that allow cybercriminals to exploit marketplace platforms. Therefore, this study suggests strengthening legal harmonization, enhancing consumer protection, improving tax regulations, and implementing effective law enforcement strategies. By integrating criminological insights into legal reforms, Indonesia can create a safer and more just online marketplace environment, contributing to sustainable digital economic development.